1986
DOI: 10.1136/ard.45.8.703
|View full text |Cite
|
Sign up to set email alerts
|

Ankylosing spondylitis, HLA-B27, and klebsiella: cross reactivity and antibody studies.

Abstract: Ankylosing spondylitis, HLA-B27, and klebsiella: cross reactivity and antibody studies SIR, The association of klebsiella with HLA-B27 involves two separate theoretical models which have been the subject of some debate, recently discussed by Singh et al,'

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…of HLA-B27 (Ebringer and Ghuloom, 1986;Ciccia et al, 2009Ciccia et al, , 2014Ciccia et al, , 2015Wright et al, 2016). Intestinal flora imbalance can also mediate host metabolism and immune function imbalance via a series of cytokines, thus participating in the pathogenesis and progress of AS.…”
Section: Metagenomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…of HLA-B27 (Ebringer and Ghuloom, 1986;Ciccia et al, 2009Ciccia et al, , 2014Ciccia et al, , 2015Wright et al, 2016). Intestinal flora imbalance can also mediate host metabolism and immune function imbalance via a series of cytokines, thus participating in the pathogenesis and progress of AS.…”
Section: Metagenomicsmentioning
confidence: 99%
“…Several studies have investigated how the microbiome as a key role in driving the pathogenesis of AS. Intestinal dysbacteriosis may affect the permeability of the intestinal wall, the expression of related inflammatory factors, the intestinal mucosal immune status in AS patients, and molecular mimicry of HLA-B27 ( Ebringer and Ghuloom, 1986 ; Ciccia et al, 2009 , 2014 , 2015 ; Wright et al, 2016 ). Intestinal flora imbalance can also mediate host metabolism and immune function imbalance via a series of cytokines, thus participating in the pathogenesis and progress of AS.…”
Section: Metagenomicsmentioning
confidence: 99%
“…Ebringer et al. ( 38 ) believed that there was molecular mimicry between HLA-B27 and some bacterial antigen components in the intestinal tract of patients with AS (such AS the polypeptide structure of Klebsiella and Shigella ). In vitro , bacterial peptides from AS-enriched species triggered an increase of interferon (IFN)-γ producing cells, mimicking type II collagen.…”
Section: Possible Mechanisms Of the Gut Microbiome Promoting The Deve...mentioning
confidence: 99%
“…The high homology led to the hypothesis that bacterial HSP60 might induce a break in immune tolerance as a result of molecular mimicry leading to autoimmunity 4 . Cross-reactivity between bacterial and human antigens was first suggested by Ebringer et al who in an attempt to link the presence of antibodies to Klebsiella and recurrent inflammation in AS, suggested that linear or conformational epitopes common to microbial antigens and host cell molecules would give rise to autoimmunity through an immune cross-reaction 5 . In the case of Ebringer et al, it was suggested that the crossreaction was between a component of gram-negative bacteria and human leukocyte antigen B27 (HLA-B27) as this antigen was found to be a major susceptibility gene for AS 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…Cross-reactivity between bacterial and human antigens was first suggested by Ebringer et al who in an attempt to link the presence of antibodies to Klebsiella and recurrent inflammation in AS, suggested that linear or conformational epitopes common to microbial antigens and host cell molecules would give rise to autoimmunity through an immune cross-reaction 5 . In the case of Ebringer et al, it was suggested that the crossreaction was between a component of gram-negative bacteria and human leukocyte antigen B27 (HLA-B27) as this antigen was found to be a major susceptibility gene for AS 5,6 . HLA-B27 *Corresponding author Email: tc@hst.aau.dk encodes the � 1 domain in a cell surface molecule named major histocompatibility complex (MHC) class I.…”
Section: Introductionmentioning
confidence: 99%